Microstructural evolution of helium-irradiated 6H–SiC subjected to different irradiation conditions and annealing temperatures: A multiple characterization study. (December 2019) - Daghbouj, N.; Li, B.S.; Callisti, M.; Sen, H.S.; Karlik, M.; Polcar, T.
Abstract: The microstructural phenomena occurring in 6H–SiC subjected to different irradiation conditions and annealing temperatures were investigated to assess the suitability of 6H–SiC as a structural material for nuclear applications. To this aim, a single crystal of 6H–SiC was subjected to He + irradiation at 300 keV with different fluences and at temperatures ranging from 25 to 750 °C. Rutherford backscattering/channeling (RBS/C), X-ray diffraction (XRD) and transmission electron microscopy (TEM) analyses were combined to shed light on the microstructural changes induced by irradiation and subsequent annealing (750 to 1500 °C). At room temperature, amorphization starts to occur at a fluence of 2.5 × 10 16  cm −2 (0.66 dpa). On the contrary, amorphization was prevented at high irradiation temperatures and fluences. Furthermore, a thin and highly strained region located around the maximum He concentration (Rp) formed. This region results from the accumulation of interstitial atoms which are driven toward the highly damaged region under the actions of a strain gradient and high temperature. Regardless of the fluence and irradiation temperature, the material stores elastic energy, which leads to the trapping of He in dissimilar defect geometries. For irradiation temperatures below 750 °C, helium was accumulated in bubbles which coarsened after annealing. On the other hand, for an irradiation temperature of 750 °C, helium was trapped in platelets (even for medium fluence), which evolved into a homogeneous dense array of cavities during annealing. DFT calculations show that the bubbles are under high pressure and contribute to developing the overall tensile strain in the single crystal 6H–SiC. Graphical abstract: Image, graphical abstract